2007
DOI: 10.28945/223
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Access: An Analysis of the Influence of the E-Rate Program in Bridging the Digital Divide in American Schools

Abstract: Executive SummaryE-Rate is a U.S. federal funding program for providing discounts for telecommunications, Internet access and internal networking costs for schools and libraries to ensure access equity across poor and rich, rural, urban and suburban areas, and highly served and underserved areas. This paper examines the impact of the E-Rate program on social equity and educational efficacy in American public schools, based upon the federal government's original purpose for investment. The investigation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The importance of high-speed Internet connectivity for national, organizational and individual interests has long been recognized. Thus, supporting this highspeed infrastructure is seen as crucial for the US's economic and political future relative to its international peers (Federal Communications Commission (FCC), 2010;Hausman, 1994;Jaeger, 2005;Park & Chong, 2007). Those with broadband connectivity will be advantaged -domestically and abroad.…”
Section: Objectives or Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of high-speed Internet connectivity for national, organizational and individual interests has long been recognized. Thus, supporting this highspeed infrastructure is seen as crucial for the US's economic and political future relative to its international peers (Federal Communications Commission (FCC), 2010;Hausman, 1994;Jaeger, 2005;Park & Chong, 2007). Those with broadband connectivity will be advantaged -domestically and abroad.…”
Section: Objectives or Purposesmentioning
confidence: 99%
“…As our jobs, entertainment, politics and even health care move online, millions are at risk of being left behind" (Crawford, 2011).Households without either broadband or dial-up Internet cite lack of need (47 percent), lack of affordability (24 percent), and an inadequate computer (15 percent) as key reasons for their non-adoption of the service, and indicated that they use work, school, libraries, and others' homes for alternative Internet access (U.S. Department of Commerce, 2011).The importance of high-speed Internet connectivity for national, organizational and individual interests has long been recognized. Thus, supporting this highspeed infrastructure is seen as crucial for the US's economic and political future relative to its international peers (Federal Communications Commission (FCC), 2010;Hausman, 1994;Jaeger, 2005;Park & Chong, 2007). Those with broadband connectivity will be advantaged -domestically and abroad.…”
mentioning
confidence: 99%
“…Governments need to provide assistance to regions and areas where household incomes are significantly lower than the national and provincial average to make learning conditions more equitable (Li, X., 2008). In this respect, Chinese can learn from Americans who have an education rate policy as part of the Telecommunications Act of 1996 to promote digital equity (Park, Sinha, & Chong, 2007).…”
Section: Challenges and Recommendationsmentioning
confidence: 99%